Interface pressure between socket and residual limb in prosthesis with seal-in X5 and dermo liner during level ground, stairs, and ramp walking /Sadeeq Ali - Sadeeq, Ali (2015)
Transtibial amputation patients need prosthetic devices in order to regain their functional mobility and appearance. The socket and its design play a significant role in determining the wearer’s quality of the fit..Prosthetic users experience pressure between the socket and residual limb during daily activities. The underlying soft tissues and skin of the residual limb are not accustomed to weight bearing; thus, there is the risk of degenerative tissue ulcer in the residual limb because of constant or repetitive peak pressure applied by the socket. The prosthetic users experience different pathways such as level ground, ramps, stairs and other uneven surfaces during their daily activities. An amputee is greatly affected when dealing with the environmental barriers such as slopes and stairs because of the reported high interface pressure between socket and residual limb. The interface pressure between the residual limb and prosthetic socket has a significant effect on an amputee’s satisfaction and comfort. Suspension system and socket fitting in prosthetic devices significantly affect the amputee’s comfort, mobility, and satisfaction. Prosthetic users required a comfortable liner, good suspension, and quality socket to avoid skin problems and to prevent discomfort while using the prosthesis for daily activities. Liners provide a comfortable interface by adding a soft cushion between the residual limb and the socket. Dermo and Seal-In X5 liners are two new interface systems and, due to their relative infancy, no literature were found about their interface pressure during level walking as well as stairs and ramp negotiations and their effect on patient’s satisfaction. Therefore, the objectives of this study was to compare the interface pressure for these two liners during level walking as well as stairs and ramp negotiations and their effect on patients satisfaction and to compare it with the most common liner in today use (Pelite liner) and its effect on patient’s satisfaction and perceived problems. In addition, investigation were carried out on the effect of suspension system on patient satisfaction and perceived problems associated with thethree liners.The selection of good prosthetic liner presents a challenging task in amputee rehabilitation. Two prostheses were fabricated for each of the10 amputees, one with the Seal-In X5 liner and one with the Dermo liner for comparison between Dermo, Pelite, and Seal-In X5 liners, 60 prostheses were fabricated. Interface pressure was measured during level walking, stairs and ramp negotiations. Each subject filled in a Prosthetic Evaluation Questionnaire (PEQ) questionnaire regarding his satisfaction with the three liners. Mean Peak Pressure (MPP) was significantly (P<0.05) low with Dermo liner during level walking as well as stairs and ramp negotiations compared with Seal-In X5 Liner. Participants were significantly (P<0.05) satisfied and fewer problems were recorded with Dermo liner compared with Seal-In X5 and Pelite liners. Hence, it can be concluded that the Dermo liner provides more comfortable socket-residual limb interface than the Seal-In X5 liner and showed that the Dermo liner is the best choice for transtibial users. However, despite these results, the Seal-In X5 liner offers better suspension.These results will help the clinicians and prosthetic practitioners in selecting of prosthetic liners and will also help the clinician in the fabricating of a good comfortable socket for transtibial users.three liners.The selection of good prosthetic liner presents a challenging task in amputee rehabilitation. Two prostheses were fabricated for each of the10 amputees, one with the Seal-In X5 liner and one with the Dermo liner for comparison between Dermo, Pelite, and Seal-In X5 liners, 60 prostheses were fabricated. Interface pressure was measured during level walking, stairs and ramp negotiations. Each subject filled in a Prosthetic Evaluation Questionnaire (PEQ) questionnaire regarding his satisfaction with the three liners. Mean Peak Pressure (MPP) was significantly (P<0.05) low with Dermo liner during level walking as well as stairs and ramp negotiations compared with Seal-In X5 Liner. Participants were significantly (P<0.05) satisfied and fewer problems were recorded with Dermo liner compared with Seal-In X5 and Pelite liners. Hence, it can be concluded that the Dermo liner provides more comfortable socket-residual limb interface than the Seal-In X5 liner and showed that the Dermo liner is the best choice for transtibial users. However, despite these results, the Seal-In X5 liner offers better suspension.These results will help the clinicians and prosthetic practitioners in selecting of prosthetic liners and will also help the clinician in the fabricating of a good comfortable socket for transtibial users.